Studying the Oncolytic Activity of Streptococcus pyogenes Strains Against Hepatoma, Glioma, and Pancreatic Cancer In Vitro and In Vivo - Anna N. Tsapieva; Alexander N. Chernov; Nadezhda V. Duplik; Anastasiya O. Morozova; Tatiana A. Filatenkova; Mariia A. Suvorova; Elena Egidarova; Elvira S. Galimova; Kseniya Bogatireva; Alexander N. Suvorov (Microorganisms)
Background: Cancer remains a leading cause of mortality globally. Conventional treatment modalities, including radiation and chemotherapy, often fall short of achieving complete remission, highlighting the critical need for novel therapeutic strategies. One promising approach involves the oncolytic potential of Group A Streptococcus (GAS) strains for tumor treatment. This study aimed to investigate the oncolytic efficacy of S. pyogenes GUR and its M protein knockout mutant, S. pyogenes strain GURSA1, which was genetically constructed to minimize overall toxicity, against mouse hepatoma 22A, pancreatic cancer PANC02, and human glioma U251 cells, both in vitro and in vivo, using the C57BL/6 mouse model. Methods: The in vitro oncolytic cytotoxic activity of GAS strains was studied against human glioma U251, pancreatic cancer PANC02, murine hepatoma 22a, and normal skin fibroblast cells using the MTT assay and the real-time xCELLigence system. A syngeneic mouse model of hepatoma and pancreatic cancer was used to evaluate the in vivo oncolytic effect of GAS strains. Statistical analysis was conducted using Student’s t-test and Mann–Whitney U-test with GraphPad Prism software. Results: The in vitro model showed that the live S. pyogenes GUR strain had a strong cytotoxic effect (67.4 ± 1.9%) against pancreatic cancer PANC02 cells. This strain exhibited moderate (38.0 ± 1.8%) and weak (16.3 ± 5.4%) oncolytic activities against glioma and hepatoma cells, respectively. In contrast, the S. pyogenes GURSA1 strain demonstrated strong (86.5 ± 1.6%) and moderate (36.5 ± 1.8%) oncolytic activities against glioma and hepatoma cells. Additionally, the S. pyogenes GURSA1 strain did not exhibit cytotoxic activity against healthy skin fibroblast cells (cell viability 104.2 ± 1.3%, p = 0.2542). We demonstrated that tumor treatment with S. pyogenes GURSA1 significantly increased the lifespan of C57BL/6 mice with hepatoma (34 days, p = 0.040) and pancreatic cancer (32 days, p = 0.039) relative to the control groups (24 and 28 days, respectively). Increased lifespan was accompanied by a slowdown in tumor progression, as evidenced by a reduction in the growth of hepatoma and pancreatic cancer tumors under treatment with GAS strains in mice. Conclusions: Both S. pyogenes GUR and S. pyogenes GURSA1 strains demonstrated strong oncolytic activity against murine hepatoma 22a, pancreatic cancer PANC02, and human U251 glioma cells in vitro. In contrast, S. pyogenes GUR and GURSA1 did not show toxicity against human normal skin fibroblasts. The overall survival rate and lifespan of mice treated with S. pyogenes GURSA1, a strain lacking the M protein on its surface, were significantly higher compared to the control and S. pyogenes GUR strain groups.